Outcomes of cardiac resynchronization therapy (CRT) in cardiac sarcoidosis patients with a range of ejection fractions - Alexander Liu; Raheel Ahmed; Mansimran Singh Dulay; Joseph Okafor; Alessia Azzu; Kamleshun Ramphul; Rui Shi; Gerald Ballo; John Arun Baksi; Kshama Wechalekar; Rajdeep Khattar; Peter Collins; et al. (ESC Heart Failure)
Abstract Aims In cardiac sarcoidosis (CS) patients, the benefit of cardiac resynchronization therapy (CRT) remains unclear. We sought to assess the short‐term and long‐term effects of CRT in CS patients with a range of left ventricular (LV) ejection fractions (LVEFs). Methods Consecutive CS patients with heart failure with reduced ejection fraction (HFrEF; LVEF ≤ 40%), mildly reduced ejection fraction (HFmrEF; LVEF 41%–49%) and preserved ejection fraction (HFpEF; LVEF ≥ 50) treated with CRT under the care of a tertiary UK centre between 2008 and 2023 were reviewed. CRT response was defined by >5% improvement in serial LVEF. The primary endpoint was a composite of all‐cause mortality, cardiac transplantation or unplanned hospitalization for decompensated heart failure. The secondary endpoint included ventricular arrhythmic events. Results Of the 100 patients enrolled (age 58 ± 10 years; 71% male), 63 had HFrEF, 17 had HFmrEF and 20 had HFpEF. After short‐term follow‐up (9.8 ± 5.4 months), HFrEF patients demonstrated significant LVEF response (P < 0.01). On Kaplan–Meier analysis (follow‐up 38 ± 32 months), HFrEF non‐responders had significantly worse event‐free survival compared with HFrEF responders for the primary (P < 0.001) and secondary (P = 0.001) endpoints. Despite short‐term LV function improvement, CRT responders still had worse event‐free survival compared with HFmrEF/HFpEF patients for the primary endpoint (P < 0.001). On multivariable Cox analysis, age [hazard ratio (HR) 1.05, 95% confidence interval (CI) 1.01–1.10, P = 0.008] and HFrEF CRT non‐response (HR 12.33, 95% CI 2.45–61.87, P = 0.002) were associated with the primary endpoint. Conclusions In CS patients with HFrEF, CRT response is associated with a better long‐term prognosis than non‐response. However, HFrEF CRT responders still have worse long‐term prognosis than HFmrEF/HFpEF patients.